Imbibition and vigor of chemically scarified Poncirus trifoliata seeds - Catraro, Marcela Andrea; Poggi, Damián René; Quadrelli, Agustín Ricardo; García, Leonardo Martín; Gariglio, Norberto Francisco; Flores, Patricia Cecilia (Association of Official Seed Analysts and the Society of Commercial Seed Technologists, 2019)
Poncirus trifoliata is the most important rootstock in citrus production in Argentina. The seeds exhibit slow and uneven germination due to physical dormancy associated with the presence of seed coats. The objectives of this research were to select the most efficient chemical scarification procedures for P. trifoliata seeds, and assess the effects of such procedures on imbibition and vigor. A first experiment was conducted to assess the efficiency of three chemical scarification methods and their effects on seed vigor. Vigor was determined as the germination velocity index (GVI) and mean time to maximum germination (MTMG). A second experiment was conducted to assess seed vigor and the role of seed coats in imbibition, by comparing the most effective chemical scarification method identified in the first experiment to manual removal of both seed coats and no removal of seed coats. Percentage germination, the vigor indices GVI and MTMG, and the conductivity test (CT) were determined. Scarification with sodium hypochlorite showed the best results. The imbibition curve of seeds with both seed coats reflected an exponential weight increase, seeds with only the testa removed had a linear weight increase, whereas fresh weight of seeds with both testa and tegmen removed followed a hyperbolic change. CT indicated that chemically scarified seeds had no significant increase in conductivity compared to seeds with intact seed coats. Scarification with sodium hypochlorite was the most effective treatment for removing the testa and also improved seed vigor.